Early Vasopressor Initiation as an Independent Determinant of Survival in Septic Shock: A Multicenter Real-World Causal Inference Analysis - Hassan , Ahmed; Al-Faisal, Khalid; Al-Harbi, Faisal (Journal of Society Medicine, 2026)
Introduction: Septic shock is a life-threatening syndrome characterized by profound circulatory failure and dysregulated host response, with mortality remaining unacceptably high despite advances in critical care. Rapid restoration of perfusion pressure is central to resuscitation, and current guidelines advocate prompt vasopressor initiation to avoid hypotension. However, the survival benefit of early vasopressor administration remains uncertain. Methods: We conducted a multicenter retrospective cohort study of adult patients with septic shock defined according to the Sepsis-3 criteria. The primary exposure was the time from shock recognition to vasopressor initiation, categorized as early (≤X hours) versus delayed (>X hours), with complementary continuous-time analyses. The primary outcome was 28-day all-cause mortality. Secondary outcomes included ICU and hospital length of stay, vasopressor duration, organ support utilization, cumulative fluid balance, and adverse events (AEs). Multivariable adjustment was combined with propensity score–based inverse probability weighting, balance diagnostics, multiple imputation, and prespecified sensitivity analyses. Results: Among 2,184 patients, 1,042 received early vasopressor initiation and 1,142 received delayed initiation of vasopressor therapy. The unadjusted 28-day mortality rates were 27.8% and 34.6%, respectively. After adjustment, early vasopressor initiation was independently associated with lower mortality (adjusted OR 0.74, 95% CI 0.62–0.88; P<0.001). Early initiation was also associated with shorter ICU stay, reduced vasopressor duration, and lower 24-hour cumulative fluid balance without increased arrhythmia or ischemic complications. Conclusion: Early vasopressor initiation following shock recognition was independently associated with improved short-term survival, supporting a pragmatic guideline-aligned strategy that prioritizes timely hemodynamic stabilization while minimizing delays in vasopressor administration.